Catalytic hydroconversion of Lingwu bituminous coal over Fe-S/γ-Al2O3. (1st January 2014) - Yu, Li-Cheng; Wei, Xian-Yong; Wang, Ying-Hua; Zhang, Dong-Dong; Wen, Zhe; Zong, Zhi-Min; Fan, Xing; Zhao, Yun-Peng
Fe-S/γ-Al2 O3 was prepared by thermally decomposing Fe(CO)5 onto γ-Al2 O3 and subsequent sulphurisation with sublimed sulphur in a magnetically stirred autoclave and used as the catalyst for catalytic hydroconversion (CHC) of Lingwu bituminous coal (LBC). Non-catalytic hydroconversion (NCHC) and CHC of LBC were conducted in cyclohexane under 5 MPa of initial hydrogen pressure at 300°C. The reaction mixtures were extracted with petroleum ether and analysed with a gas chromatography/mass spectrometer. The results show that Fe-S/γ-Al2 O3 significantly catalysed the formation of hydroarenes, arenes and arenols and completely removed 2, 5-dimethylthiophene from LBC.